Effect of acute intermittent hypoxia on motor function in individuals with chronic spinal cord injury following ibuprofen pretreatment: A pilot study. (4th May 2017) - Lynch, Meaghan; Duffell, Lynsey; Sandhu, Milap; Srivatsan, Sudarshan; Deatsch, Kelly; Kessler, Allison; Mitchell, Gordon S.; Jayaraman, Arun; Rymer, William Zev
Abstract : Introduction : Acute intermittent hypoxia (AIH) enhances lower extremity motor function in humans with chronic incomplete spinal cord injury (SCI). AIH-induced spinal plasticity is inhibited by systemic inflammation in animal models. Since SCI is frequently associated with systemic inflammation in humans, we tested the hypothesis that pretreatment with the anti-inflammatory agent ibuprofen enhances the effects of AIH. Methods : A randomized, double-blinded, placebo-controlled crossover design was used. Nine adults (mean age 51.1 ± 13.1 years) with chronic motor-incomplete SCI (7.7 ± 6.3 years post-injury) received a single dose of ibuprofen (800 mg) or placebo, 90 minutes prior to AIH. For AIH, 9% O2 for 90 seconds was interspersed with 21% O2 for 60 seconds. Maximal voluntary ankle plantar flexion isometric torque was assessed prior to, and at 0, 30, and 60 minutes post-AIH. Surface electromyography (EMG) of plantar flexor muscles was also recorded. Results : Torque increased significantly after AIH at 30 (P = 0.007; by ∼20%) and 60 (P < 0.001; by ∼30%) minutes post-AIH versus baseline. Ibuprofen did not augment the effects of AIH. EMG activity did not increase significantly after AIH; however, there was a significant association between increases in torque and EMG in both gastrocnemius (R 2  = 0.17, P < 0.005) and soleus (R 2  = 0.17, P < 0.005) muscles. Conclusions : AIH systematically increased lower extremity torque in individuals with chronic incomplete SCI, but there was no significant effect of ibuprofen pretreatment. Our study re-confirms the ability of AIH to enhance leg strength in persons with chronic incomplete SCI.